The Dynamic of Poverty in Germany 1985-1995: Which Factors Influence the Duration of a Spell of Poverty? - Maria Rosario Gonzalez Rodriguez; Domingo Martin Martin (European Regional Science Association (ERSA), 2006)
Since the seventies most of the research which quantifies poverty and inequality of income has been carried out in the short-term using an annual household budget survey. Recently, the availability of Panel data has facilitated the appearance of longitudinal studies. The objective of our research is to carry out a dynamic analysis of poverty and to know which factors influence the duration of a spell of poverty. The data we will use is from the Paco Panel Comparability Project. This data was collected and elaborated by the Human Capital and Mobility Programme.
Keywords: 330